STRATEGI IKLAN DIGITAL APARTEMEN VASAKA SOLTERRA PADA PLATFORM INSTAGRAM DAN YOUTUBE SHORTS - Alvira Maudi Rahmat; Alfi Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital media has encouraged the property industry to optimize marketing communication strategies through measurable digital advertising tailored to audience characteristics. This study aims to explain the digital advertising strategy of Vasaka Solterra Apartment on Instagram Reels and YouTube Shorts using the media planning theory. The research employed a descriptive qualitative method through observation, active participation, literature study, and analysis of Instagram Ads and YouTube Shorts Ads insights. The findings show that the main target audience is individuals aged 25–34 years, with Jakarta as the primary target area on Instagram Ads and several major cities as secondary targets on YouTube Shorts Ads. Media objectives were developed based on the AIDA stages: Attention, Interest, Desire, and Action. Instagram Ads were more effective in generating leads through marketing contact messages, while YouTube Shorts Ads were more effective in increasing audience awareness and reach. Platform selection, budget allocation, seven-day pulsing scheduling, and performance evaluation indicate that media planning strategies can support more targeted advertising message distribution. The study recommends strengthening call-to-Action strategies and refining audience targeting to improve lead generation effectiveness.